Antecedents and outcomes of service recovery satisfaction: perspectives on open and distance learning in Malaysia - Mohd Rushidi Mohd Amin,; Shishi Kumar Piaralal, (2020)
Researchers and practitioners in higher education often pay less attention to service recovery compared to service quality or customer satisfaction particularly in the context of open and distance learning (ODL) in Malaysia. More importantly, the outcomes of service recovery satisfaction are often given less emphasis by the ODL institutions and often focused on delivering services with the approach of getting it right the first time. Service failure is inevitable and when the service delivery fails at some point, the whole process will be disrupted, and the students will be dissatisfied. This is where service recovery through justice dimensions play its part. In this study, the relationship between justice dimensions (procedural, distribution, interpersonal and informational justice), service recovery satisfaction, and behavioural outcomes are being explored and the moderating effects of corporate image in the Malaysian ODL context are also being looked at and examined in this study. (Abstract by authors)